Are the users of social networking sites homogeneous? A cross-cultural study - ALARCÓN-DEL-AMO, MARÍA-DEL-CARMEN; GÓMEZ-BORJA, MIGUEL-ÁNGEL; LORENZO-ROMERO, CARLOTA (Frontiers in Psychology, 2015)
The growing use of Social Networking Sites (SNS) around the world has made it necessary to understand individuals’ behaviours within these sites according to different cultures. Based on a comparative study between two different European countries (The Netherlands versus Spain), a comparison of typologies of networked Internet users has been obtained through a latent segmentation approach. These typologies are based on the frequency with which users perform different activities, their socio-demographic variables, and experience in social networking and interaction patterns. The findings show new insights regarding international segmentation in order to analyse SNS user behaviours in both countries. These results are relevant for marketing strategists eager to use the communication potential of networked individuals and for marketers willing to explore the potential of online networking as a low cost and a highly efficient alternative to traditional networking approaches. For most businesses, expert users could be valuable opinion leaders and potential brand influencers.